LncRNA HAND2-AS1 inhibits non-small cell lung cancer migration, invasion and maintains cell stemness through the interactions with TGF-β1. Issue 1 (11th January 2019) - Miao, Feng; Chen, Ji; Shi, Meng; Song, Yang; Chen, Zhiming; Pang, Liewen
Abstract : LncRNA HAND2-AS1 is characterized as a tumor suppressor involved in several types of malignancies, but its role in non-small cell lung cancer (NSCLC) is unknown. Our study was carried out to investigate the involvement of lncRNA HAND2-AS1 in NSCLC. In our study, we observed that levels of HAND2-AS1 were lower in tumor tissues than that in adjacent healthy tissues. Compared with healthy controls, plasma levels of HAND2-AS1 were lower, while levels of transforming growth factor β (TGF-β) were higher in NSCLC patients. A significant negative correlation between plasma levels of HAND2-AS1 and TGF-β1 was found in NSCLC patients but not in healthy controls. LncRNA HAND2-AS1 overexpression inhibits, while exogenous TGF-β1 treatment promotes cell migration and invasion ability and cancer cell stemness. Cancer cells with lncRNA HAND2-AS1 overexpression showed down-regulated TGF-β1, while TGF-β1 treatment showed no significant effects on lncRNA HAND2-AS1 expression. TGF-β1 attenuated the inhibitory effects of lncRNA HAND2-AS1 overexpression on cell migration, invasion and stemness. We concluded that lncRNA HAND2-AS1 may regulate the migration, invasion and stemness of NSCLC cells through interactions with TGF-β1.